Residual activity after radioembolization of liver tumours with 90Y resin microspheres - Ahmadzadehfar, H.; Haslerud, T.; Reichmann, K.; Meyer, C.; Habibi, E.; Fimmers, R.; Muckle, M.; Sabet, A.; Biersack, H.J.; Ezziddin, S. (Nuklearmedizin - NuclearMedicine, 2014)
The actual number of resin microspheres is approximately 30-60 times higher than glass microspheres per 3 GBq vial. Thus, radioembolization (RE) with resin microspheres exerts an embolization effect besides the radiation effect. This embolization effect can occasionally cause early back flow of the microspheres before application of the entire calculated dose. To avoid these adverse side effects, RE has to be terminated at an earlier time point. Measurement of the residual activity in the delivery box, which includes the v-vial, tube and catheter, to calculate the achieved target dose is often challenging. The aim of the current study was to establish a post-RE measurement method comparable to the glass microspheres method without unnecessary radiation exposure to the staff and risk of contamination. Methods: Two different measurements were performed. First, total radioactivity in the shipping vial was measured in an ion chamber and then it was put in the delivery box and the radiation was measured from a 30 cm distance from the centre of the box with a dosimeter. The required radioactivity was then transferred to the v-vial, and the shipping vial was measured again. After that, the v-vial was measured from the same distance from the centre of the box with dosimeter. Results: Altogether 62 times the shipping vial with different activities were measured with a significant positive correlation between the amount of the activity measured in the iron chamber and the radiation dose, measured with dosimeter (r2 = 0.98; p < 0.001). There was also a strong positive correlation between these measurements of the v-vial (r2 = 0.98; p < 0.001). Conclusion: With measurement of the residual activity in the delivery box using a dosimeter the percentage of the whole injected activity can be easily calculated. This facilitates the calculation of the actual, achieved target and non-target dose in those cases, where therapy had to be stopped because of eminent flow reversal or obstruction.
Keywords: Radioembolization; dosimetry; 90Y-microspheres; resin microspheres